Comprehensive Analysis of Chloroplast Genomes in Leguminous Forage Species: Codon Usage, Phylogenetic Relationships, and Evolutionary Insights - Rui Yang; Ying Xue; Xiaofan He; Tiejun Zhang (Agronomy)
Leguminous forages play critical roles in sustainable agriculture and ecosystem management by enhancing soil fertility through nitrogen fixation and providing high-quality protein for livestock. This study sequenced and assembled the chloroplast genome of Thermopsis alpina using high-throughput sequencing technology. Along with 29 other leguminous forage species obtained from the NCBI database, we conducted comprehensive analyses of the chloroplast genome of 30 species, focusing on their codon usage patterns, phylogenetic relationships, and evolutionary dynamics. The results revealed that the chloroplast genome of Thermopsis alpina exhibits a typical quadripartite structure, with a total length of 153,714 bp, encoding 124 genes and comprising a large single-copy region (LSC, 83,818 bp), a small single-copy region (SSC, 17,558 bp), and two inverted repeat regions (IRs, 26,169 bp). Relative synonymous codon usage (RSCU) analysis revealed 28 preferred codons, predominantly terminating in A/U, with a notable preference for the leucine codon UUA across all species. Additionally, the effective number of codons (ENC) and the PR2 plot analysis suggest a weak codon usage bias, primarily shaped by selective pressures rather than mutational forces. Simple sequence repeat (SSR) analysis shows a notable concentration of SSRs in intergenic regions, highlighting their potential role in genome stability and evolution. Phylogenetic tree construction based on chloroplast genome data further uncovers the genetic relationships and evolutionary trajectories within the leguminous forage species. Overall, these findings provide valuable insights into the molecular evolution of leguminous forages and offer a theoretical basis for their improved utilization in sustainable agricultural practices and ecological restoration.